ANALISIS CUSTOMER TRUST DAN CUSTOMER EXPERIENCE DALAM MENENTUKAN LOYALITAS JAMAAH UMRAH PADA PT ARRAFSYAH SAFARI HARAMAIN - Hasnidar Hasnidar; Muhammad Ilham Wardhana Haeruddin; Azlan Azhari (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
The Umrah travel industry in Indonesia, particularly in Makassar, is experiencing rapid growth but faces challenges such as intense competition, fraud issues, and increasing consumer demands for service quality. In this context, customer trust and customer experience are crucial factors in building Umrah pilgrim loyalty. This study aims to analyze the influence of customer trust and customer experience on loyalty through customer satisfaction as a mediating variable among pilgrims at PT Arrafsyah Safari Haramain in Makassar. The research method employed a quantitative approach with survey techniques and data analysis using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that customer experience significantly influences pilgrim satisfaction and loyalty, while customer trust has no significant effect on satisfaction but a positive effect on loyalty. Furthermore, satisfaction has been shown to play a significant role as a mediator in the relationship between customer experience and loyalty. These findings emphasize that Umrah travel agencies need to prioritize improving the overall customer experience, while maintaining trust, to build long-term pilgrim loyalty.